2017
DOI: 10.1038/s41598-017-05285-1
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced MR microscopy of amyloid plaques in five mouse models of amyloidosis and in human Alzheimer’s disease brains

Abstract: Gadolinium (Gd)-stained MRI is based on Gd contrast agent (CA) administration into the brain parenchyma. The strong signal increase induced by Gd CA can be converted into resolution enhancement to record microscopic MR images. Moreover, inhomogeneous distribution of the Gd CA in the brain improves the contrast between different tissues and provides new contrasts in MR images. Gd-stained MRI detects amyloid plaques, one of the microscopic lesions of Alzheimer’s disease (AD), in APPSL/PS1M146L mice or in primate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 55 publications
(72 reference statements)
2
29
0
Order By: Relevance
“…The minimum plaque size detected in histology was around 3 µm, whereas the smallest plaques detected in OCT were around 12 µm. While the detected size of plaques in all modalities did agree with earlier literature reports [44][45][46], the direct comparison between histology and OCT (Figures 5a and 7) showed that OCT seems to severely overestimate plaque size. Potential reasons for this could be the expansion (convolution) of imaged objects by the imaging system's point spread function (PSF), the inherently different contrast mechanisms and tissue shrinkage due to dehydration and fixation processes.…”
Section: Discussionsupporting
confidence: 89%
“…The minimum plaque size detected in histology was around 3 µm, whereas the smallest plaques detected in OCT were around 12 µm. While the detected size of plaques in all modalities did agree with earlier literature reports [44][45][46], the direct comparison between histology and OCT (Figures 5a and 7) showed that OCT seems to severely overestimate plaque size. Potential reasons for this could be the expansion (convolution) of imaged objects by the imaging system's point spread function (PSF), the inherently different contrast mechanisms and tissue shrinkage due to dehydration and fixation processes.…”
Section: Discussionsupporting
confidence: 89%
“…Although some of these non-fibrillary amyloids and their toxicity have been described in vitro, and different oligomeric species have been isolated from affected brain homogenates [1][2][3] , the challenge remains regarding their identification in vivo and the time at which they form, presumably long before the appearance of neurological deficits. Whereas powerful imaging techniques such as MRI and PET are being used to detect the presence of fibrillary amyloids, and in some cases, oligomeric species have been targeted [4][5][6][7][8][9] , the detection of earlier non-fibrillary aggregates and their structural characterization, which would facilitate the design of effective drugs, remain elusive.…”
mentioning
confidence: 99%
“…3,4 A key step along the road to an early AD diagnosis would be an in vivo identification of Aβ plaques. However as the plaques are small (ranging from 10-200 µm 5 ) and located within the brain, this presents some logistical difficulties.…”
Section: Introductionmentioning
confidence: 99%